Ciclo reprodutivo, maturidade sexual e longevidade de Odontophrynus americanus (Anura: Odontophrynidae) no Sul do Brasil - Brum, Amanda Jamille Carvalho (2019)
Reproductive strategies of anuran amphibians (i.e. temporal strategies and reproductive cycles) are associated with the activity pattern and reproductive modes of the species and aims to increase its reproductive success. Sexual size dimorphism (difference in the length or body mass of sexually mature individuals), another aspect related to reproductive strategies, can be assigned to reproductive aspects (i.e. fertility), as well as to differences in the age of sexual maturity, growth rate and longevity of a species. Variation in the parameters related to the age of the individuals (e.g. age of sexual maturity, longevity) provide essential information about the life history of a species, as well as demographic data from a population. Odontophrynus americanus is a medium-sized anuran species, distributed in southern South America. This species presents the reproduction type classified as explosive, and can be found for most of the year after strong rains. Thus, the aim of this contribution is to describe the reproductive cycle, identify the age of sexual maturity and longevity of this species in southern Brazil, as well as to investigate the presence of sexual dimorphism related to size. Therefore, samples of gonads and phalanges of O. americanus were collected and submitted to histological processing. Variation in the parameters related to the age of individuals (e.g. age of sexual maturation, longevity) were investigated through the method of skeletochronology, and the presence of sexual dimorphism investigated through analysis of size and body mass. O. americanus presented a potentially continuous reproductive cycle, being able to reproduce on any season of the year. Males and females reach sexual maturity at one year, and in relation to longevity the highest value found for males was of ten years, while for females was of six years. There is no noticeable evidence of sexual dimorphism on the size (length and body mass). Knowing the primordial aspects of the life history of a species is of utmost importance, since new contributions may be based on it, allowing comparisons and possible generalizations about the evolutionary meaning of ecological strategies.